A descriptive study on brain drain of Chinese employees and professionals from China, employed in other countries - Yang, Bo (2012)
The main objective of this study is to examine the factors to influence "brain drain" in China. The three factors affect Chinese to finally decide to stay or immigrate to foreign countries. Dates were gathered from questionnaire, the respondents are all Chinese, but they are working in Malaysia. Correlation and chi square were used to examined the relationship between The result of this study shows that family bond has relationship with immigration, but it is not a strong relationship; job prospective and immigration have significant relationship; opening - free social atmosphere and immigration have a obvious relationship. The findings were discussed and recommendations in future research were also addressed